Analisa Kinerja Operasional dan Pelayanan Bus Trans Bahagia Kota Jambi Berdasarkan Tingkat Kepuasan Pengguna - Thoriq Dwi Rizqillah Dwi Rizqillah (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
This study aims to analyze the operational performance and service quality of Trans Bahagia Bus in Jambi City based on customer satisfaction. The study was conducted because several operational performance indicators have not yet met the required service standards, although Trans Bahagia Bus has become an environmentally friendly electric public transportation alternative in Jambi City. This research employed a quantitative approach by collecting data through field observations, interviews, and questionnaires distributed to 80 respondents selected using the Slovin formula. The data were analyzed using validity and reliability tests, multiple linear regression analysis, and the Customer Satisfaction Index (CSI) method.The results indicate that the load factor, headway, and waiting time have not yet met the operational standards, while travel time, travel speed, service hours, and fleet availability have complied with the established standards. The multiple linear regression analysis reveals that comfort, safety, ease of accessing the bus, route, and vehicle condition have both simultaneous and partial positive and significant effects on customer satisfaction, with a coefficient of determination (R²) of 98.3%. The variable with the greatest influence on customer satisfaction is the ease of accessing the bus. Furthermore, the Customer Satisfaction Index (CSI) value reached 90.64%, which falls into the Excellent category. Therefore, it can be concluded that passengers are generally highly satisfied with the services provided by Trans Bahagia Bus in Jambi City. Nevertheless, improvements in operational performance, particularly increasing the number of buses to reduce waiting time and headway, are still required